Italian Nurses' Attitudes Towards Neonatal Palliative Care: A Cross‐Sectional Survey. Issue 6 (18th September 2020) - Cerratti, Francesca; Tomietto, Marco; Della Pelle, Carlo; Kain, Victoria; Di Giovanni, Pamela; Rasero, Laura; Cicolini, Giancarlo
Abstract: Purpose: Neonatal palliative care becomes an option for critically ill neonates when death is inevitable. Assessing nurses' attitudes towards, barriers to, and facilitators of neonatal palliative care is essential to delivering effective nursing care. Methods: This study was conducted from January to September 2015 and involved Italian nurses employed in Level III neonatal intensive care units in 14 hospitals in northern, central, and southern Italy. A modified version of the Neonatal Palliative Care Attitudes Scale (NiPCAS) was adopted to assess nurses' attitudes. Findings: A total of 347 neonatal nurses filled out the questionnaire. The majority were female (87.6%), with a mean age of 40.38 (±8.3) years. The mean score in the "organization" factor was 2.71 (±0.96). The "resources" factor had a mean score of 2.44 (±1.00), while the "clinician" factor had a mean score of 3.36 (±0.90), indicating the main barriers to and facilitators of implementing palliative nursing care. Conclusions: Italian neonatal nurses may face different obstacles to delivering neonatal palliative care and to improve their attitudes in this field. In the Italian context, no facilitators of, only barriers to, palliative care delivery were identified. Clinical Relevance: Nurses' attitudes towards neonatal palliative care are essential to supporting nurses, who are constantly exposed to the emotional and moral distress connected with this field of end‐of‐life nursing care.